PELATIHAN BASIC PSYCHOLOGICAL FIRST AID BAGI PENATALAYANAN DI GKI GEJAYAN YOGYAKARTA - Princen, Princen; Anna, Jessica Amelia; Sidjaja, Fransisca Febriana; Simanjuntak, Erni Julianti; Polii, Gishelle Grace Villaneuve (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2024)
Mental health is a vital component of individual well-being. With the prevalence of mental disorders in Indonesia reaching around 20% of the total population, there is an urgent need to address this problem. In the context of the Special Region of Yogyakarta (DIY), the rate of serious mental and emotional disorders is quite high, indicating the importance of special attention to mental health problems. The limited number of professional mental health workers in Indonesia exacerbates this situation, so counseling services are an effective solution, including peer counseling. Gereja Kristen Indonesia (GKI) Gejayan Yogyakarta has the potential to facilitate this counseling service through basic counseling training for existing health teams and visiting teams. The training activities designed by a team of lecturers from the Faculty of Psychology, Universitas Pelita Harapan (UPH). The training consists of online and face-to-face sessions in three separate sessions over a period of three weeks, which covered basic communication and counseling techniques, Psychological First Aid (PFA), as well as role-play. The evaluation showed positive feedback from participants regarding the relevance of the material, although there were obstacles related to implementation time and participant characteristics. Overall, this training succeeded in meeting the participants' expectations and needs, and increased their interest in participating in similar programs in the future.